Ezetimibe and atherosclerotic cardiovascular disease: a systematic review and meta-analysis - Omidi, Fatemeh; Rahmannia, Maryam; Shahidi Bonjar, Amir Hashem; Mohammadsharifi, Parsa; Nasiri, Mohammad Javad; Sarmastzadeh, Tala (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Introduction: Indeed, individuals diagnosed with atherosclerotic cardiovascular disease (ACD) are exposed to an increased risk of cardiovascular events. Reducing low-density lipoprotein cholesterol (LDL-C) levels has been established as an effective approach to mitigate these risks. However, a comprehensive and up-to-date meta-analysis investigating the LDL-C-lowering effectiveness and the impact on coronary atherosclerotic plaque compositions of Ezetimibe has been lacking. Methods: We conducted a systematic review by meticulously analyzing databases such as MEDLINE, EMBASE, and the Cochrane CENTRAL for randomized controlled trials that evaluated the efficacy of ezetimibe in lowering LDL-C levels and its influence on coronary atherosclerotic plaques among individuals with ACD. This review encompassed studies available until August 1, 2023. In our analysis, we employed the weighted mean difference (WMD) as the aggregated statistical measure, accompanied by the corresponding 95% confidence interval (CI). Results: We encompassed a total of 20 eligible studies. Our findings unveiled that the combined therapy involving ezetimibe alongside statins led to a more substantial absolute decrease in LDL-C in comparison to using statins alone. This difference in means amounted to (-14.06 mg/dL; 95% CI -18.0 to -10.0; p = 0.0001). Furthermore, upon conducting subgroup analyses, it became evident that the intervention strategies proved effective in diminishing the volume of dense calcification (DC) in contrast to the control group. Conclusions: Our study findings indicate that the inclusion of ezetimibe in conjunction with statin therapy leads to a modest yet meaningful additional reduction in LDL-C levels when compared to using statins in isolation. Importantly, the introduction of ezetimibe resulted in a significant decrease in the volume of DC. However, it is worth noting that further investigation is warranted to delve deeper into this phenomenon